Implementasi Sertifikasi Halal sebagai Faktor Kunci Peningkatan Kepercayaan Konsumen terhadap Produk UMKM di Purwakarta: Penelitian - Dewi Nurhasanah, Chintia; Kemala Handayanny, Indyra; Meilani, Tanti; Syibli, Ahmad; Wahyudi, Tri (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Bakso Aci Makam Pahlawan Purwakarta is a food-processing micro business operating since 2016 with stable demand but previously lacked halal certification due to challenges such as low halal literacy, absence of halal SOPs, unverified ingredients, limited documentation, and difficulties using the SIHALAL platform. This study aimed to strengthen the UMKM’s readiness and compliance through structured assistance using the Participatory Action Research (PAR) approach, involving observation, Fishbone analysis, SJPH development, ingredient verification, SIHALAL training, administrative support, and monitoring. The results show that the UMKM successfully met all requirements, obtained BPJPH halal certification, and consistently implemented SJPH, leading to greater consumer trust, increased customers, and inspiring nearby UMKM to pursue halal certification.